Answer:
none
Step-by-step explanation:
Answer:
![\displaystyle 702](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20702)
Step-by-step explanation:
we are given a exponential function
![\displaystyle f(x) = {3}^{x + 1} - 22](https://tex.z-dn.net/?f=%20%20%5Cdisplaystyle%20f%28x%29%20%3D%20%20%7B3%7D%5E%7Bx%20%2B%201%7D%20%20-%2022)
where x represents the number and f(x) represents the amount
we are also given that when x is 3 then f(x) is 59 likewise when x is 6 then f(x) is 2165
to figure out the average rate of change between 3 and 6 we can consider the average rate of change formula given by
![\displaystyle m = \frac{ f(x)_ {2} - f(x)_{1} }{ x_{2} - x_{1} }](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20m%20%3D%20%20%5Cfrac%7B%20f%28x%29_%20%7B2%7D%20-%20%20f%28x%29_%7B1%7D%20%7D%7B%20x_%7B2%7D%20-%20%20x_%7B1%7D%20%7D%20)
substitute what we have:
![\displaystyle m = \frac{ 2165 - 59 }{6 - 3 }](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20m%20%3D%20%20%5Cfrac%7B%202165%20-%20%2059%20%7D%7B6%20-%203%20%7D%20)
simplify substitution:
![\displaystyle m = \frac{2106 }{3 }](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20m%20%3D%20%20%5Cfrac%7B2106%20%7D%7B3%20%7D%20)
simplify division:
![\displaystyle m = 702](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20m%20%3D%20%20702)
hence, the average rate of change between 3 and 6 is <u>7</u><u>0</u><u>2</u>
Answer:
a = 21
Step-by-step explanation:
If x = h is a zero of a polynomial then f(h) = 0, thus
p(-
) = 27( -
)³ - a(-
) - (-
) + 3 = 0, that is
27 (-
) -
a +
+ 3 = 0
- 1 -
a +
= 0 ( multiply through by 9 to clear the fractions )
- 9 - a + 30 = 0
- a + 21 = 0 ( subtract 21 from both sides )
- a = - 21 ( multiply both sides by - 1 )
a = 21
The summation of negative 5 n minus 1, from n equals 3 to 12 can be
expressed as
n = 3/12
substitute the value of n to the equatio
-5n – 1
-5( 3/12 ) -1
-9/4